2003
DOI: 10.1046/j.1460-9568.2003.02573.x
|View full text |Cite
|
Sign up to set email alerts
|

Agonistic encounters in aged male mouse potentiate the expression of endogenous brain NGF and BDNF: possible implication for brain progenitor cells' activation

Abstract: The condition of dominance or submission following agonistic encounters in the adult male mouse is known to differentially affect brain nerve growth factor, a neurotrophin playing a role in brain remodeling, in the fine tuning of behaviour and in the regulation of the basal forebrain cholinergic neurons. During development and adult life nerve growth factor regulates brain expression of neurotransmitters and the stimulation of progenitor cells (stem cells) which, under different external stimuli, may different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…Wu et al [128] in social defeat model in mice demonstrated impaired expressions of glucocorticoid receptors mRNA and BDNF mRNA in the hippocampus and increased level of corticotrophin-releasing hormone mRNA in hypothalamus, as well as increased levels of IL-6 and TNF- α in serum. Fiore et al [129] found that dominant animals had higher levels of BDNF mRNA in the subventricular zone and hippocampus than did subordinate animals. Conversely, subordinate animals exhibited higher levels of NGF compared with dominant animals in these neurogenic regions.…”
Section: Stress Exposure During Adulthoodmentioning
confidence: 99%
“…Wu et al [128] in social defeat model in mice demonstrated impaired expressions of glucocorticoid receptors mRNA and BDNF mRNA in the hippocampus and increased level of corticotrophin-releasing hormone mRNA in hypothalamus, as well as increased levels of IL-6 and TNF- α in serum. Fiore et al [129] found that dominant animals had higher levels of BDNF mRNA in the subventricular zone and hippocampus than did subordinate animals. Conversely, subordinate animals exhibited higher levels of NGF compared with dominant animals in these neurogenic regions.…”
Section: Stress Exposure During Adulthoodmentioning
confidence: 99%
“…Moreover, aggressive behavior can enhance the number of Ki67-positive cells in the SVZ of aged animals. This suggests that, in the aged mouse, fighting behavior may increase neurogenesis, most probably throughout proliferation and/or differentiation of brain stem cells [86], possibly contributing to reduce the neuronal damage and loss caused by prolonged GC exposure as a consequence of the social stress related to fighting [87, 88]. In addition, within the brain, the major increase in NGF following fighting has been observed in the hypothalamus a brain area involved in the activation of certain behaviors and in physiological modifications inducing changes in bodily homeostasis, suggesting a role for NGF in coping and neuroendocrine mechanisms [31].…”
Section: The Role Of Ngf At the Cnsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14] In one such in vivo study the growth factor EGF was infused into the lateral ventricle of adult mice; the results demonstrated a dramatic increase in the number of proliferating cells in the subependymal layer of the lateral ventrical. 9 Immunohistochemical analysis revealed that more than 95% of the cells present in the subependymal layer were immunopositive for the EGF receptor and were also nestin positive, a well established marker of proliferating neural progenitor cells.…”
mentioning
confidence: 99%